Above‐ground biomass is driven by mass‐ratio effects and stand structural attributes in a temperate deciduous forest. (21st September 2017) - Fotis, Alexander T.; Murphy, Stephen J.; Ricart, Raleigh D.; Krishnadas, Meghna; Whitacre, James; Wenzel, John W.; Queenborough, Simon A.; Comita, Liza S.
Abstract: Forest ecosystems are critical for the global regulation of carbon (C), a substantial portion of which is stored in above‐ground biomass (AGB). While it is well understood that taxonomic and functional composition, stand structure and environmental gradients influence spatial variation in AGB, the relative strengths of these drivers at landscape scales have not been investigated in temperate forests. Furthermore, when biodiversity enhances C storage, it is unclear whether it is through mass‐ratio effects (i.e. the dominant trait in communities regulates AGB) or through niche complementarity (i.e. increased AGB due to interspecific resource partitioning). To address these mechanisms, we analysed data from a census of 28, 262 adult trees sampled across 900 ha of temperate deciduous forest in southwestern Pennsylvania. We used data on four key plant functional traits to determine if (1) there is a positive relationship between species diversity and AGB and (2) whether this is due to mass‐ratio effects or niche complementarity. We also sought to (3) identify the physical stand structural attributes and topographic variables that influence AGB across this landscape. We found AGB was positively related to species richness and negatively related to species evenness, albeit weakly, while functional diversity indices had neutral effects. Above‐ground biomass was enhanced in communities dominated by traits related to greater maximum tree height, deeper minimum rooting depths and larger seeds. Most importantly, areas with high AGB were dominated by Acer saccharum and Liriodendron tulipifera . Overall, these results support mass‐ratio effects, with little evidence for niche complementarity. Synthesis . Stand structure, topography, and species and functional composition, but not taxonomic or functional diversity, were found to be key drivers of above‐ground biomass at landscape scales (<900 ha) in this temperate deciduous forest. Our findings suggest that simultaneously managing for both high diversity and for above‐ground carbon storage may prove challenging in some forest systems. Our results further indicate that the impact of tree biodiversity loss on above‐ground carbon stocks will depend greatly on the identity of the species that are lost. Abstract : Stand structure, topography, and species and functional composition, but not taxonomic or functional diversity, were found to be key drivers of above‐ground biomass at landscape scales (<900 ha) in this temperate deciduous forest. Our findings suggest that simultaneously managing for both high diversity and for above‐ground carbon storage may prove challenging in some forest systems. Our results further indicate that the impact of tree biodiversity loss on aboveground carbon stocks will depend greatly on the identity of the species that are lost.